Smile and be a villain : a Dorothy Martin mystery - Dams, Jeanne M. (Dams, Jeanne M. Dorothy Martin mysteries., 2016)
When Dorothy Martin and her husband, retired police detective Alan Nesbitt, decide to visit the beautiful island of Alderney in the English Channel, they hope for a pleasant, peaceful holiday. It<U+2019>s not to be. Taking a walk on their very first day, they discover a body, apparently the victim of an unfortunate accident, on a precipitous hill path. The dead man, they learn, is an American named Abercrombie who had made himself both loved and hated during his few weeks on the island. Although there is no concrete evidence of foul play, both Dorothy and Alan are uneasy about the death and decide to delve further. And then they unearth some most disquieting revelations . . .